Побудова наближеного розв’язку осесиметричної задачі динаміки неізотермічного вологопереносу - Марченко, О.О.; Самойленко, Т.А. (Кібернетика та комп’ютерні технології, 2020)
Для осесиметричної початково-крайової задачі волого- та теплопереносу із змішаними неоднорідними крайовими умовами отримано оцінки швидкості збіжності неперервного за часом та дискретного наближених розв'язків, побудованих на базі методу скінченних елементів. The purpose of the paper is to formulate the appropriate generalized problem in the Galorkin form for the axisymmetric initial-boundary value problem. The important goal is to investigate the accuracy of the continuous in time and completely discrete approximate generalized solutions based on the finite elements method. Results. The algorithm for constructing of approximate generalized solution of the axisymmetric initial-boundary value problem for the system of filtration and heat transfer equations is proposed. The estimates of the convergence rate for the continuous in time and discrete approximate solutions based on the finite elements method are obtained. Цель статьи: для поставленной осесимметричной начально-краевой задачи сформулировать соответствующую обобщенную задачу в форме Галеркина и исследовать точность построенных методом конечных элементов непрерывного по времени и полностью дискретного приближенных обобщенных решений. Результаты. Предложен алгоритм построения приближенного обобщенного решения осесимметричной начально-краевой задачи для системы уравнений влаго- и теплопереноса, которая моделирует нестационарные неизотермические процессы во влажных грунтах. Получены оценки скорости сходимости непрерывного по времени и дискретного приближенных решений, построенных методом конечных элементов.